Adjunct Strategies for Tuberculosis Vaccines: Modulating Key Immune Cell Regulatory Mechanisms to Potentiate Vaccination - Jayashankar, Lakshmi; Hafner, Richard (Frontiers in Immunology, 2016)
Tuberculosis remains a global health threat of alarming proportions, resulting in 1.5 million deaths worldwide. The only available licensed vaccine, BCG, does not confer lifelong protection against active TB. To date, development of an effective vaccine against TB has proven to be elusive, and devising newer approaches for improved vaccination outcomes is an essential goal. Insights gained over the last several years have revealed multiple mechanisms of immune manipulation by Mtb in infected macrophages and dendritic cells that support disease progression and block development of protective immunity. This review provides an assessment of the known immunoregulatory mechanisms altered by Mtb, and how new interventions may reverse these effects. Examples include blocking of inhibitory immune cell co-receptor checkpoints (e.g. PD-1). Conversely, immune mechanisms that strengthen immune cell effector functions may be enhanced by interventions, including stimulatory immune cell co-receptors (e.g., OX40). Modification of the activity of key cell “immunometabolism” signaling pathway molecules, including mTOR, GSK3β, wnt/β-catenin, AMPK and sirtuins, related epigenetic changes, and preventing induction of immune regulatory cells (e.g., Tregs, MDSCs) are powerful new approaches to improve vaccine responses. Interventions to favorably modulate these components have been studied primarily in oncology to induce efficient anti-tumor immune responses, often by potentiation of cancer vaccines. These agents include antibodies and a rapidly increasing number of small molecule drug classes that have contributed to the dramatic immune-based advances in treatment of cancer and other diseases. Because immune responses to malignancies and to Mtb share many similar mechanisms, studies to improve TB vaccine responses using interventions based on “immuno-oncology” are needed to guide possible repurposing. Understanding regulation of immune cell functions appropriated by Mtb to promote the imbalance between protective and pathogenic immune responses may guide development of innovative drug-based adjunct approaches to substantially enhance the clinical efficacy of TB vaccines.